La tutoría y su relación con el desarrollo socio-afectivo en los estudiantes de la I.E Serafin Filomeno - Cieza Rodrigo, Jorge (2013)
Research mentoring and its relationship with socio- emotional development in students of School "Serafín Filomena" of Moyobamba, 2012, investigates the correlation between the two phenomena (mentoring and emotional development), and the main objective was to establish the relationship between mentoring with socio- emotional development in students of School "Serafín Filomena" of Moyobamba, 2012, and the specific objectives were to identify the tutorial level areas , learning sessions and theme that is taught to students of School "Serafín Filomena" , identify the level of emotional development in the social, interpersonal and intrapersonal students of School "Serafín Filomena" in the third quarter and determine the relationship betweeri mentoring with socio- emotional development in students of School "Serafín Filomena" . The tutorial is based on Delgado and Barrenechea (2005), Segovia and Fresco (2000), Pastor (1995) and the Ministry of Education (2005), state that tries to cover this area needs students in the dimensions academic, personal, vocational, social welfare, culture and coexistence, and socio- emotional development in Gonzales (2009), Dovecote and Teruel (2009), and Alcantar (2002), that affect the socialization of human beings in relation to its context. These frames give sufficient references theoretical tools to pose the following hypothesis: There is a relationship between mentoring with socio- emotional development in students of School "Serafín Filomena" of Moyobamba, 2012. Methodologically, the research design is descriptive and correlational study, with a sample of 276 students of the educational institution "Serafín Filomena", and in the process of statistical analysis was obtained accepting the research hypothesis with a calculated value of te = 8, 79 and a value tabular t, = ± 1, 96 , verifying that the calculated value is greater than the tabular right, which enables the null be located within the rejection region.